Synthesis and characterization of EFB clinker supported nickel and cobalt catalysts for methane dry reforming - Han Jie, Chan (2015)
Methane dry reforming is environmental friendly due to the potential sequestration of CO2. Therefore, substantial research works have been carried out to develop reforming catalysts that exhibit high catalytic performance and excellent longevity. The current work reports on the synthesis of 20wt%Co/80wt%EFB clinker and 20wt%Ni/80wt%EFB clinker catalysts via wet-impregnation technique, followed by various characterization techniques such as BET, XRD, XRF, TGA and FESEM. The BET specific surface area of Co/EFB clinker and Ni/EFB clinker catalyst were 2.83 m2g-1 and 2.37 m2g-1, respectively. In addition, XRD diffractogram of EFB clinker showed two highest peaks at around 2θ = 27.2° and 31.5°, which can be attributed to CaO and K2O species, respectively. This finding was also consistent with XRF analysis where potassium (K) and calcium (Ca) were positively identified. Subsequently, methane dry reforming studies revealed that Ni/EFB clinker catalyst always yielded higher formation rates of H2 and CO. Indeed, the rate was maximum at CO2:CH4 feed ratio of unity. The average conversion of CH4 for reactions using Co/EFB clinker and Ni/EFB clinker catalyst are obtained to be 78.26 % and 78.19 % respectively. Meanwhile, the average conversion of CO2 for reactions using Co/EFB clinker and Ni/EFB clinker catalyst are 80.40 % and 81.17 % respectively. When reaction temperatures were varied, the activation energy over Co/EFB clinker was 124.4 kJ mol-1 while that for the reaction over the Ni/EFB clinker catalyst was 113.0 kJ mol-1. Post reforming reaction, oxidation profiles of the used catalysts indicated carbon-free condition. This was corroborated by the FESEM images for both sets of used catalysts, where no carbon whisker was found.